Covered self-expanding metal stent use in the pancreatic duct: a case series - Akbar, A.; Baron, T. H. (Endoscopy, 2012)
Plastic stents have been used in the pancreatic duct for a variety of indications. However, unlike in the bile duct, the use of covered self-expanding metal stents (CSEMSs) has been discouraged because multiple side branches drain into main pancreatic duct (MPD) and the ductal diameter is relatively small. This report aims to describe our experience using CSEMSs in the pancreatic duct in a series of nine patients, with special focus on adverse events. Indications were strictures (n = 5), intraductal mucinous neoplasm (IMPN; n = 1), pancreatic duct leak (n = 1), disconnected duct syndrome (n = 1), and severe acute pancreatitis/necrosis with disrupted duct (n = 1). Eight patients had symptomatic improvement, or radiological resolution of or improvement in their strictures, leaks, perforation, and necrosis. Two of these have indwelling CSEMSs for ongoing treatment. One patient (disconnected duct syndrome) was considered a treatment failure as the stent migrated and the patient underwent distal pancreatectomy for refractory pain. Two patients underwent pancreaticoduodenectomy for their malignancies after their CSEMSs had been in place for 43 and 49 days, respectively. Importantly no patients, including those with indwelling CSEMSs, developed stent-related acute pancreatitis with a median follow-up of 4 months. One patient developed post-procedure pain requiring hospitalization for 1 day. Median stent duration was 77 days. These observations suggest there is a potential role for the use of CSEMSs in the MPD in selected patients with pancreatic pathology.